The Phenomenon of Marriage Trust Issues in the Millennial Generation from A Psychological Perspective Communication in Medan City - Syifa Urahmah; Lusiana Andriani Lubis; Iskandar Zulkarnain (International Journal of Scientific Multidisciplinary Research, 2024)
This research aims to analyze the phenomenon of trust issues in marriage among millennials in the city of Medan, the impact of these trust issues, and the attitudes of millennials in dealing with this phenomenon. The paradigm employed is constructivism with a phenomenological method; the research object is trust issues in marriage, and the research subjects are millennials. The research informants consist of six individuals and three triangulation informants, with the information received resulting in data saturation. Data collection techniques include in-depth interviews and observations. The findings of this study indicate that marital trust issues are caused by a lack of effective communication between partners, leading to conflicts and trauma from partner betrayal, infidelity, abusive behavior, and lack of parental approval. This phenomenon is also driven by insufficient family roles, shifts in cultural values of marriage, and the negative impact of social media. Marital trust issues result in difficulties in self-disclosure, delays in marriage, and changes in values related to marriage. The attitudes developed to avoid similar experiences include improving communication with partners, enhancing trust in partners, being selective in choosing partners, and maintaining a positive mindset